Fibrinogen Adsorption, Platelet Adhesion and Thrombin Generation at Heparinized Surfaces Exposed to Flowing Blood - Keuren, Jeffrey F. W.; Wielders, Simone J. H.; Willems, George M.; Morra, Marco; Lindhout, Theo (Thrombosis and Haemostasis, 2002)
Thrombus formation at an artificial surface in contact with blood is a complex process that encompasses accretion of platelets from flowing blood and fibrin deposition. Platelet adhesion and fibrin formation are intimately intertwined reactions that are triggered by different sets of surface adsorbed plasma proteins. To dissect the contribution of protein adsorption and platelet adhesion to thrombin formation, a coherent study was performed with non-coated (NC) and heparin-coated (HC) surfaces. Thrombin production in whole blood, platelet adhesion and protein adsorption were studied using an amidolytic thrombin assay, a dynamic platelet adhesion assay and ellipsometry, respectively. Thrombin generation in flowing whole blood exposed to HC surfaces was greatly diminished when compared with NC surfaces. However, separate platelet adhesion and protein adsorption studies with anticoagulated whole blood revealed that platelets do not adhere because fibrinogen is not available in the protein layer that was deposited during the perfusion. These findings indicate that the in vitro thrombogenicity of a material cannot be predicted from platelet adhesion and protein adsorption data when these measurements are performed with anticoagulated blood or platelet rich plasma. Preincubation of NC and HC surfaces with fibrinogen or 2000-fold diluted plasma resulted in similar amounts of surface-bound fibrinogen and mediated massive platelet adhesion from flowing whole blood. These results indicate that a) platelet adhesion correlates with the availability of surface-bound fibrinogen and b) NC and HC surfaces are indistinguishable with respect to protein (fibrinogen) adsorption and platelet adhesion. It is apparent that the heparinized surface used in our studies exerts its anti-thrombogenic properties by neutralizing locally formed thrombin and not by reducing fibrinogen-dependent platelet adhesion.
Keywords: Heparin coating; artificial surface; fibrinogen; platelets; thrombin